Ni bon, ni mauvais. L’élève entre-deux en lecture écriture à l’école primaire - Yolande Peigné (Recherches en Éducation)
While learning the written language, middle-range pupils call out my attention as an experienced school teacher. As a matter of fact, these neither good nor bad pupils with fluctuating results go unnoticed by their teachers throughout the Primary School years. Will they not swell up/increase the statistics of the poor reading/writing results of the Citizenship Day Defense or coming out of Highschool? Middle-range pupils are those, aged between 7 and 10, who obtain 24 to 36 correct answers out of 60 for the 2009 and 2012 National Assessments are available: interviews with teachers (for pupils aged 8 and 11 years old ); studying the national assessments results using a systemic and development of their reasoning. The results go beyond the model and lead me to study further way in the path of working memory and skills.